Enhancement of Curcumin Bioavailability Using Nanocellulose Reinforced Chitosan Hydrogel - Gunathilake, T.M.S.U.; Ching, Yern Chee; Chuah, Cheng Hock (MDPI, 2017)
A unique biodegradable, superporous, swellable and pH sensitive nanocellulose reinforced chitosan hydrogel with dynamic mechanical properties was prepared for oral administration of curcumin. Curcumin, a less water-soluble drug was used due to the fact that the fast swellable, superporous hydrogel could release a water-insoluble drug to a great extent. CO2 gas foaming was used to fabricate hydrogel as it eradicates using organic solvents. Field emission scanning electron microscope images revealed that the pore size significantly increased with the formation of widely interconnected porous structure in gas foamed hydrogels. The maximum compression of pure chitosan hydrogel was 25.9 ± 1 kPa and it increased to 38.4 ± 1 kPa with the introduction of 0.5% cellulose nanocrystals. In vitro degradation of hydrogels was found dependent on the swelling ratio and the amount of CNC of the hydrogel. All the hydrogels showed maximum swelling ratios greater than 300%. The 0.5% CNC-chitosan hydrogel showed the highest swelling ratio of 438% ± 11%. FTIR spectrum indicated that there is no interaction between drug and ingredients present in hydrogels. The drug release occurred in non-Fickian (anomalous) manner in simulated gastric medium. The drug release profiles of hydrogels are consistent with the data obtained from the swelling studies. After gas foaming of the hydrogel, the drug loading efficiency increased from 41% ± 2.4% to 50% ± 2.0% and release increased from 0.74 to 1.06 mg/L. The drug release data showed good fitting to Ritger-Peppas model. Moreover, the results revealed that the drug maintained its chemical activity after in vitro release. According to the results of this study, CNC reinforced chitosan hydrogel can be suggested to improve the bioavailability of curcumin for the absorption from stomach and upper intestinal tract.